2019
DOI: 10.1103/physrevx.9.021021
|View full text |Cite
|
Sign up to set email alerts
|

Density Wave Probes Cuprate Quantum Phase Transition

Abstract: In cuprates, the strong correlations in proximity to the antiferromagnetic Mott insulating state give rise to an array of unconventional phenomena beyond high temperature superconductivity. Developing a complete description of the ground state evolution is crucial to decoding the complex phase diagram. Here we use the structure of broken translational symmetry, namely d-form factor charge modulations in (Bi,Pb)2(Sr,La)2CuO 6+δ , as a probe of the ground state reorganization that occurs at the transition from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 60 publications
3
32
1
Order By: Relevance
“…1(c) we plot the Fourier transform (FT) of the dI/dV map in Figs. 1(b), which was widely utilized to determine the modulation wavevector of charge orders in cuprates [5,7,23,36]. The Bragg peaks of the atomic lattice are marked by solid red circles in the FT map, whereas the broad peak circled in blue indicates the wavevector QCO  0.21 (2π/a0), corresponding to a wavelength CO  4.8 a0 of the long-range checkerboard charge order along the Cu-O direction.…”
Section: A Checkerboard Charge Order In the Optimally Doped Samplementioning
confidence: 99%
See 2 more Smart Citations
“…1(c) we plot the Fourier transform (FT) of the dI/dV map in Figs. 1(b), which was widely utilized to determine the modulation wavevector of charge orders in cuprates [5,7,23,36]. The Bragg peaks of the atomic lattice are marked by solid red circles in the FT map, whereas the broad peak circled in blue indicates the wavevector QCO  0.21 (2π/a0), corresponding to a wavelength CO  4.8 a0 of the long-range checkerboard charge order along the Cu-O direction.…”
Section: A Checkerboard Charge Order In the Optimally Doped Samplementioning
confidence: 99%
“…Most previous STM studies on the charge order focused on underdoped and optimally doped cuprates with a well-defined pseudogap phase. It was found that the checkerboard pattern with 4 a0 periodicity (a0 is the lattice constant ~3.8 Å) is the first electronic order that emerges when doping holes into the parent Mott insulator [22], and it persists to hole density close to optimal doping [23]. With further doping into the overdoped regime, resonant x-ray scattering [9] and STM experiments [23] reported the persistence of checkerboard order with increasing wavelength up to 10 a0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Scenario 2: q 0 locks to 1/4 in YBCO, the fundamental wave vector invoked for Bi-based cuprates [21][22][23], but in order to reach q 0.32, discommensurations are so frequent that the charge modulation is effectively best described as a period-3 CDW for π/2 DCs or a CDW with a period-6 motif for π DCs, as shown in Figs. 6c,e.…”
Section: Discussionmentioning
confidence: 99%
“…This view has been challenged by recent progress in the analysis of scanning tunnelling microscopy (STM) measurements in Bi-based cuprates revealing an extended doping range in which the local wave vector q 0 is 1/4 (in units of 2π a , with a being the crystal lattice parameter), equivalent to a local commensurate period λ = 4a [21][22][23][24][25]. Mesaros et al have taken this as evidence that there is a universal instability towards the formation of a period-four density wave, fundamentally rooted in strong-correlation physics [21].…”
mentioning
confidence: 99%